2015
DOI: 10.1038/nrclinonc.2015.132
|View full text |Cite
|
Sign up to set email alerts
|

Does surgery have a role in managing incurable gastric cancer?

Abstract: Although the incidence of gastric cancer is decreasing, the outcomes of this disease are among the poorest of all solid-organ tumours, predominantly due to the frequent presence of stage IV metastatic disease at primary presentation. Stage IV gastric cancer is incurable and carries a very poor prognosis (5-year survival rate of ∼4%); palliative chemotherapy remains the standard of care, but increasing evidence indicates that palliative surgery can provide a prognostic and symptomatic benefit, particularly in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 53 publications
1
81
0
1
Order By: Relevance
“…[12] Current strategies usually define stage 0 to III gastric cancer as curable, which is suitable for radical resection. For patients of stage IV, the curative opportunity may be limited, as it is reported that up to 50% of patients without metastatic disease who undergo “curative” surgical resection present with recurrent disease within 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Current strategies usually define stage 0 to III gastric cancer as curable, which is suitable for radical resection. For patients of stage IV, the curative opportunity may be limited, as it is reported that up to 50% of patients without metastatic disease who undergo “curative” surgical resection present with recurrent disease within 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 70% of gastric cancer occurs in the developing world [3] and gastric cancer new case and mortality were the highest in China according to the WHO world cancer report 2014. Although recent advancement in gastric cancer early detection, therapy, and prevention partly enhanced survival rate of early gastric cancer, Stage IV gastric cancer is still incurable with a very poor 5-year survival rate of approximately 4~5% [4]. The curative procedure of gastric cancer is still not satisfactory because the early gastric cancer was difficulty to discover in clinic [5].…”
Section: Introductionmentioning
confidence: 99%
“…Lauren’s classification identifies two main histotypes of GC, intestinal and diffuse [2]. GC patients remain a primary clinical challenge despite recent improvements in the diagnostic, surgical, and therapeutic opportunities for GC [3, 4]. …”
Section: Introductionmentioning
confidence: 99%